Excel 2019 bible - Alexander, Michael 1972-; Kusleika, Dick; Walkenbach, John (John Wiley & Sons, 2019)
The complete guide to Excel 2019 Whether you are just starting out or an Excel novice, the Excel 2019 Bible is your comprehensive, go-to guide for all your Excel 2019 needs. Whether you use Excel at work or at home, you will be guided through the powerful new features and capabilities to take full advantage of what the updated version offers. Learn to incorporate templates, implement formulas, create pivot tables, analyze data, and much more. Navigate this powerful tool for business, home management, technical work, and much more with the only resource you need, Excel 2019 Bible.-Create functional spreadsheets that work; -Master formulas, formatting, pivot tables, and more; -Get acquainted with Excel 2019's new features and tools. Whether you need a walkthrough tutorial or an easy-to-navigate desk reference, the Excel 2019 Bible has you covered with complete coverage and clear expert guidance.--Provided by publisher.